2007
DOI: 10.1016/j.cryobiol.2007.08.010
|View full text |Cite
|
Sign up to set email alerts
|

Anti-ice nucleation activity in xylem extracts from trees that contain deep supercooling xylem parenchyma cells

Abstract: Boreal hardwood species, including Japanese white birch (Betula platyphylla Sukat.var. japonica Hara), Japanese chestnut (Castanea crenata Sieb. et Zucc.), katsura tree (Cercidiphyllum japonicum Sieb. et Zucc.), Siebold's beech (Fagus crenata Blume), mulberry (Morus bombycis Koidz.) and Japanese rowan (Sorbus commixta Hedl.), had xylem parenchyma cells (XPCs) that adapt to subfreezing temperatures by deep supercooling. Crude extracts from xylem in all these trees were found to have anti-ice nucleation activity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 40 publications
1
16
0
Order By: Relevance
“…Crude extracts from xylem tissues that include deep supercooling XPCs in several hardwood species including katsura tree exhibited supercooling-facilitating capability in solutions containing the ice nucleation bacterium (INB) Erwinia ananas [12]. Furthermore, novel types of supercooling-facilitating substances were identified in crude xylem extracts from katsura tree [11].…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Crude extracts from xylem tissues that include deep supercooling XPCs in several hardwood species including katsura tree exhibited supercooling-facilitating capability in solutions containing the ice nucleation bacterium (INB) Erwinia ananas [12]. Furthermore, novel types of supercooling-facilitating substances were identified in crude xylem extracts from katsura tree [11].…”
Section: Introductionmentioning
confidence: 97%
“…It was found in previous studies that in already-reported supercooling-facilitating substances, the supercooling capability changes depending on the kinds of ice nucleator 7 in solutions [12,25,26]. Therefore in order to elucidate the effect of flavonol glycosides on control of supercooling capability in XPCs, it is necessary to determine the effects of these flavonol glycosides on solutions containing different kinds of ice nucleators.…”
Section: Introductionmentioning
confidence: 99%
“…This result indicated that SCF activity varied depending on the structure even among polyphenols. Kasuga et al 2007 reported that different active compounds suppressed different ice nuclei, but the level of their activity was influenced by the structural characteristics of ice nuclei. When the allyl group was removed from eugenol, the SCF activity decreased by 1.70 , and when the methoxy group was removed, its activity decreased by 0.70 Kawahara et al 1996a .…”
Section: Characterization Of Scf Activity Of Caffeinementioning
confidence: 99%
“…Current climate change and the effects on cold-hardy insects has been discussed by Bale and Hayward (2010) who also include a brief overview of the supercooling abilities of over-wintering insects. The supercooling abilities of some plants, including trees, are discussed in Kasuga et al (2007) and a general overview of nucleation and anti-nucleation in biological systems is given by Zachariassen and Kristiansen (2000).…”
Section: Supercooling In Biological Systemsmentioning
confidence: 99%
“…In biological systems some plant cells adapt to subfreezing temperatures by deep supercooling, with temperatures as low as -60 °C reported (Kasuga et al 2007(Kasuga et al , 2010. In the case of insects it has been shown that most have the ability to supercool in the absence of gut content, but this does not automatically mean that they cold-hardy (Bale andHayward 2010, Doucet et al 2009).…”
Section: Introductionmentioning
confidence: 99%